ANALISIS EMPIRIS PERKEMBANGAN BENTUK BADAN HUKUM LEMBAGA AMIL ZAKAT DALAM PENGELOLAAN ZAKAT DI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Rifki Imamudin; Tubagus Rifqy Thantawi; Susi Melinasari (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The potential for zakat in Indonesia is very large. This can be seen from the people who are predominantly Muslim. Zakat has become a must for Muslims. This is the main capital in developing zakat in Indonesia. However, this must be supported by collection to distribution so that it is right on target and according to its purpose. One of the supports is the establishment of the Amil Zakat Institution (LAZ) to manage zakat funds. In addition, the role of the government is also needed as the giver of authority for the formation of the legal entity Amil Zakat Institution. This research aims to determine and analyze the effect of the level of knowledge of zakat and various government policies in supporting the development of the legal entity form of the Amil Zakat Institution, especially in the people of Pamijahan District, Bogor Regency. This research uses quantitative research methods. Based on the results of the research conducted, it can be seen that if the level of zakat knowledge and policies issued by the government have increased, then it can increase the development of the legal form of the Amil Zakat Institution in the people of Pamijahan District, Bogor Regency.